Online and Blended Communities of Inquiry: Exploring the Developmental and Perceptional Differences - Akyol, Zehra; Garrison, D. Randy; Ozden, M. Yasar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This paper discusses findings of a mixed method approach to a study of the development of a community of inquiry in an online and a blended learning environment. A graduate course delivered online and in a blended format was the context of the study. Data were gathered from the Community of Inquiry Survey, transcript analysis of online discussions, and interviews with students and the course instructor. Using multiple qualitative and quantitative data sources, the goal was to explore the developmental differences of the three presences (social, teaching, and cognitive) in the community of inquiry framework and students’ perceptions of a community of inquiry. The results indicated that in both the online and blended course a community of inquiry developed and students could sense each presence. However, the findings revealed developmental differences in social and cognitive presence between the two course formats with higher perceptions in the blended course.